Potential role of the bitter taste receptor T2R14 in the prolonged survival and enhanced chemoresponsiveness induced by apigenin - Stern, Louisa; Boehme, Lukas Fabian; Goetz, Mara Rebecca; Nitschke, Christine; Giannou, Anastasios; Zhang, Tao; Güngör, Cenap; Reeh, Matthias; Izbicki, Jakob Robert; Fliegert, Ralf; Hausen, Anne; Giese, Nathalia; et al. (International journal of oncology, 2023)
Bitter taste receptors (T2Rs) are G protein‑coupled receptors originally detected in the gustatory system. More recently, T2Rs have been shown to be expressed in extra‑oral cells eliciting non‑gustatory functions. Emerging evidence has suggested a potential role for T2R signaling in diverse pathophysiological conditions, including cancer. The aim of the present study was to evaluate the expression of T2R14 in pancreatic ductal adenocarcinoma (PDAC) and to assess its involvement in the anticancer effects induced by apigenin, a natural ligand of T2R14. For this purpose, T2R14 expression was explored in PDAC tumor tissue and tumor‑derived cell lines. Using the cell lines expressing the highest levels of T2R14, its effects on chemoresponsiveness and migration upon activation with apigenin were investigated in vitro. To the best of our knowledge, the present study was the first to confirm the expression of the T2R family member T2R14 in PDAC. Patients with relatively high levels of T2R14 expression exhibited significantly prolonged overall survival compared with that of patients with low T2R14 expression. Furthermore, novel functions for apigenin were revealed; notably, apigenin was shown to elicit cytotoxic, anti‑migratory and chemosensitizing effects to 5‑fluoruracil (5‑FU) and to 5‑FU, leucovorin, irinotecan and oxaliplatin in pancreatic cancer cells. In conclusion, the present study extended the evidence for the anticancer effects of apigenin and strongly indicated the functional relevance of T2R14 in PDAC, even though their respective underlying pathways appear to be independent of each other.
Published online on: November 15, 2022
Gesehen am 13.02.2023